Classroom Quality Management in Improving the Learning Motivation of Fifth Grade Students in Elementary School - Fitriyana Fitriyana; Ahmad Sukandar (Journal of Innovation and Research in Primary Education, 2026)
This study investigates how systematic classroom quality management enhances fifth-grade student learning motivation in Indonesian elementary schools. Despite established policy frameworks emphasizing quality management standards, significant gaps persist between policy intentions and classroom realities, particularly regarding the integration of industrial quality management principles into educational practice. Employing a qualitative case study approach, this research examined classroom quality management processes at SDN Kertaraharja and SDN Ciadeg in Cianjur Regency. Data were collected through classroom observations, semi-structured interviews with principals (n=2), teachers (n=6), and students (n=12), and document analysis. Findings reveal that systematic implementation of Deming's PDCA cycle—encompassing strategic planning with student voice integration, responsive implementation utilizing varied interactive methods, continuous evaluation tracking both academic and motivational outcomes, and adaptive follow-up—significantly enhances student learning motivation. Student participation increased from 62% to 87% during interactive activities, with unexpected emergence of spontaneous peer teaching behaviors indicating heightened intrinsic motivation. Key obstacles included limited facilities, insufficient teacher training, and resource constraints, overcome through creative solutions and collaborative approaches. This research contributes theoretically by validating industrial quality management frameworks in educational contexts and practically by providing replicable models for resource-constrained schools. The study demonstrates that educational quality enhancement is achievable through systematic, collaborative approaches recognizing student motivation as both a process indicator and valued outcome.